2020
DOI: 10.1016/j.bmcl.2019.126788
|View full text |Cite
|
Sign up to set email alerts
|

Further exploration of the structure-activity relationship of imidazoquinolines; identification of potent C7-substituted imidazoquinolines

Abstract: Small molecule agonists of TLR7/8, such as imidazoquinolines, are validated agonists for the treatment of cancer and for use in vaccine adjuvants. Imidazoquinolines have been extensively modified to understand the structure-activity relationship (SAR) at the N1-and C2-positions resulting in the clinical drug imiquimod, resiquimod, and several other highly potent analogues. However, the SAR of the aryl ring has not been fully elucidated in the literature. This initial study examines the SAR of C7-substituted im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…As outlined in Scheme 1, compounds 5a−c were treated with 70% HNO 3 in propionic acid to obtain the 3-nitroquinolinols (6a−c). 42 Next, 6a−c were chlorinated using POCl 3 and the products 7a−c were obtained via carefully quenching the excess POCl 3 . In the next step, the ipsodisplacement of chloro functionality with substituted benzyl amines were carried out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined in Scheme 1, compounds 5a−c were treated with 70% HNO 3 in propionic acid to obtain the 3-nitroquinolinols (6a−c). 42 Next, 6a−c were chlorinated using POCl 3 and the products 7a−c were obtained via carefully quenching the excess POCl 3 . In the next step, the ipsodisplacement of chloro functionality with substituted benzyl amines were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis was started from the commercially available quinolin-4-ol ( 5a ) and its methoxy derivatives ( 5b and 5c ). As outlined in Scheme , compounds 5a – c were treated with 70% HNO 3 in propionic acid to obtain the 3-nitroquinolinols ( 6a – c ) . Next, 6a – c were chlorinated using POCl 3 and the products 7a – c were obtained via carefully quenching the excess POCl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Hunt et al 77 reported a library of compounds to explore the C-7 aryl position by imposing different electrondonating groups (EDGs) and electron-withdrawing groups (EWGs) as well as hydrogen acceptors and donors such as cyano (40), chloro (41), methoxy (42), and hydroxy (43), whereas the substitutions on N-1 and C-2 were based on the previously known SAR. In general, the SAR indicated that the EDGs at the 3.5.…”
Section: Structural Evolution and Structure−activity Relationship Of ...mentioning
confidence: 99%
“…The fruitful combination of these two pharmacophores could achieve imidazoquinoline derivatives and be utilized for various applications, such as modulating the phosphodiesterase and adenosine A3 receptors, high toll-like receptor 7/8 (TLR7/TLR8) selective agonists, anticancer efficacy, etc. [ 14 , 15 ]. Molecular docking studies are used as a potential tool to identify the various TLR and other residues interacting with small molecular imidazoquinoline derivatives [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%